Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-12-19T11:14:46+01:00
Y=-2(x+7)(x-12)

-2(x+7)(x-12) = 0 wtedy i tylko wtedy gdy
x+7=0 lub x-12=0 czyli
x=-7 lub x= 12
2 5 2
2009-12-19T11:16:01+01:00
Y=-2(x+7)(x-12) = -2(x² + 7x - 12x - 84) = -2(x² - 5x - 84)
x² - 5x - 84 = 0
Δ = 25 - 336 = 361
pierwiastek z Δ = 19
x1 = 5 - 19/2 = -14/2 = -7
x2 = 5 + 19/2 = 24/2 = 12
1 1 1
2009-12-19T11:26:18+01:00
Y=-2(x+7)(x-12)
y=-2(x²-12x+7x-84)
y=-2x²+24x-14x+168
y=-2x²+10x+168
-2x²+10x+168=0/÷2
-x²+5x+84=0
Δ=b²-4ac=5²-4×(-1)×84=25+336=361
x₁=-b-√Δ/2a=-5-√361/2×(-1)=-5-19/-2=-24/-2=12
x₂=-b+√Δ/2a=-5+√361/2×(-1)=-5+19/-2=14/-2=-7